The Development of Learning Media for the Kinetic Theory of Gases Using the ADDIE Model with Augmented Reality - Rifqa Gusmida; Nur Islami (Journal of Educational Sciences, 2017)
For senior high school students, learning concepts in physics is increasingly more difficult when the topic is abstract and cannot be seen with the unaided eye. The research here utilized augmented reality technology and instructional design following the ADDIE model (analysis, design, development, implementation and evaluation) to develop learning media for physics, specifically the kinetic theory of gases. Preliminary analysis was conducted in a senior high school to evaluate the challenges students face when learning physics. The design of the media was based on addressing problems that the students were having. Augmented reality technology was then utilized and the implementation aimed to incorporate the physics concepts into the product. The media was evaluated by six experts. Finally, the learning media presented real-time 3D animation of gas kinetic theory with three basic competencies relevant to the topic. In the final validation, the results indicated that the developed learning media had a validity value of 3.55 out of four-point scale and good quality outcomes. As such, the developed media regarding the kinetic theory of gases is valid and effective for the process of learning and teaching. It is ready to be tested and used in actual learning environments.